2007
DOI: 10.1097/mlg.0b013e3181255ec4
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric and Engineering Analysis of the Septal L‐Strut

Abstract: Intrinsic elasticity of the septal cartilage, the mucoperichondrial flap, and overlap with the bony vault all contribute to the stability of the L-strut, which is enhanced by preserving a small segment of cartilage at the bony-cartilaginous junction of the dorsal L-strut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 7 publications
3
75
1
Order By: Relevance
“…A common maxim of septoplasty surgery is the preservation of a minimum of height of the remnant L-strut at 10 to 15 mm in order to preserve tip projection and prevent saddle nose deformity. 25 However, mechanical testing to assess the validity of this statement was lacking until recent years. Mau and colleagues 25 described their investigation using finite element modeling of maximal tensile stress at the bony cartilaginous junction as a function of L-strut design.…”
Section: Septummentioning
confidence: 99%
“…A common maxim of septoplasty surgery is the preservation of a minimum of height of the remnant L-strut at 10 to 15 mm in order to preserve tip projection and prevent saddle nose deformity. 25 However, mechanical testing to assess the validity of this statement was lacking until recent years. Mau and colleagues 25 described their investigation using finite element modeling of maximal tensile stress at the bony cartilaginous junction as a function of L-strut design.…”
Section: Septummentioning
confidence: 99%
“…Although advantageous for follow-up and observing for recurrent malignancy, after many years cancer free, patients can often seek a more permanent alternative (we are currently working on compassionate case where the patient refuses to wear a prosthetic nose). 1,7 Studies have also shown that there are increased infections to the wound site of patients wearing a prosthetic nose in addition to reports of physical, psychological, and social insecurities. 1,7 Allogenic sources of tissue have also been considered, 8,9 and in 2005, the first near-total facial composite transplant was reported.…”
Section: The Current Clinical Approachmentioning
confidence: 98%
“…1,7 Studies have also shown that there are increased infections to the wound site of patients wearing a prosthetic nose in addition to reports of physical, psychological, and social insecurities. 1,7 Allogenic sources of tissue have also been considered, 8,9 and in 2005, the first near-total facial composite transplant was reported. Maxillary and palatal bone was transplanted, with nasal, malar, periauricular, and periorbital soft tissues also transplanted.…”
Section: The Current Clinical Approachmentioning
confidence: 98%
See 1 more Smart Citation
“…Preserving perichondrial and periosteal continuity across the junction of the septal dorsal remnant as it transitions to septal bone may serve to increase stability. 5 At the posterior septal angle, the caudal septum must be dissected free from the tough attachments to the nasal spine and maxillary crest. The deviated portion of the L-strut is then incised and removed, leaving a cephalic, dorsal remnant of septum in the midline.…”
Section: Surgical Techniquementioning
confidence: 99%